THE EFFECT OF TEACHING AT THE RIGHT LEVEL (TARL) APPROACH ON STUDENTS' NUMERACY ABILITY - Mia Octaviani Suwignyo; Ayu Tsurayya (Jurnal Math-UMB.EDU, 2025)
The numeracy ability of students in Indonesia is still relatively low. This condition encourages the need to apply a more adaptive learning approach, such as the Teaching at the Right Level (TaRL) approach. Therefore, this study aims to examine the effect of the application of the TaRL approach on improving the numeracy ability of class X students at SMAN 65 Jakarta. The method used is a quantitative research with a true-experimental approach to pretest-posttest control group design. Data were analyzed from pre-posttests using simple statistical and regression tests. After analysis, the results showed that the TaRL approach significantly improved the numeracy ability of the students, as shown by the posttest scores of the experimental group being higher than the control group. Keywords: Numeracy Ability, Teaching at the Right Level (TaRL), Pretest-Posttest